CHI '14 Extended Abstracts on Human Factors in Computing Systems 2014
DOI: 10.1145/2559206.2581208
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interactive visual simulations on learning statistics

Abstract: In previous studies non-interactive visual simulations in learning tasks have improved learners' conceptual understanding of statistical principles. To explore the impact of interactive visual simulations on conceptual understanding of statistical principles, an online tutorial where students could either manipulate or only observe changes of statistical graphs was developed. Overall, the tutorial supports students in learning statistical concepts immediately after working with the tutorial and two weeks after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Learning outcome was considered in terms of accurate answers and the time spent while learning [13,44,45]. Two statistical concepts, namely Cohen's d and the standard normal distribution (see Figures 1 and 2), were selected from the basic statistics course taught by the faculty of psychology at FernUniversität in Hagen in Germany [46].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Learning outcome was considered in terms of accurate answers and the time spent while learning [13,44,45]. Two statistical concepts, namely Cohen's d and the standard normal distribution (see Figures 1 and 2), were selected from the basic statistics course taught by the faculty of psychology at FernUniversität in Hagen in Germany [46].…”
Section: Methodsmentioning
confidence: 99%
“…They found that working with simulations enriched the classroom experience but did not improve the gain in comprehension. Iten et al [13] compared the learning outcome and learning time when using interactive simulations rather than static pictures for learning statistics. The results showed that the learning outcome was similar in both groups, but the learning time was shorter in the interactive simulation group compared with the static group.…”
Section: Statistics Learning With Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of programming, misconceptions can be defined as an incorrect understanding of a concept or a set of concepts that leads to making mistakes in writing or reading programs (Sorva, 2008). Research in other domains, such as physics (Edelsbrunner et al, 2018) or statistics (Iten, 2014), showed that learning about misconceptions can improve teaching a given subject. Research into misconceptions in the field of programming has mostly been focussed on adults in the past, therefore studies and assessments for children are still comparatively sparse.…”
Section: Introductionmentioning
confidence: 99%